Renewable Energy Powered Autonomous Smart Ocean Surface Vehicles (REASOSE) - Kamalahasan, M.; Raghu, T.; Swapna, B.; Saravanan, K.; Manjula, D. (International Journal of Integrated Engineering, 2022)
The REASOSE is not just an Ocean surface vehicle, its poly-type smart autonomous propulsion which eliminates the limitations of existing surface vehicles (remotely operated). The renewable energy source always proved to be abundance of availability in the environment, since the power created through renewable source with loss is engineering acceptance which can immobilise the vehicle. But REASOSE is a unique vehicle with poly-type propulsion incorporated with different renewable sources from the environment which furnishes the consistency of the vehicle inevitable. The REASOSE is a smart intelligent system of vehicle that autonomously switch over to the efficient propulsion as per the availability and in kind of any hindrances the vehicle acts smartly and reaches its destination contiguously. The proposed project novelty is not only stick to a line, the proposed vehicle serves to be change over for versatile applications, the vehicle will be incorporated with high definition live transmitted camera serves for coastal surveillance, deep sea monitoring and so on. The integrated CTD, ADCP and other oceanographic sensors can be a changeover in data collection at different area at required region and time. The stack-up space provides the transportation during unconditional or conditional mode of cargo transfer to required destination.